Understanding the Basics of Educational Research (Types of Research and Research Ethics) - Nia Nurmalasari; Tedi Priatna; Bayu Bambang Nur Fauzi; Nisa Santiana; Nenden Putri Rahayu; Naila Faza Ihsan (Al-Alim: Jurnal Pendidikan Agama Islam, 2026)
This research aims to understand and examine more deeply the basics of educational research, which includes types of research and research ethics in the educational context. This research uses the library research method. The aim of this article is to examine in more depth the basic concepts of educational research, the types of research classified, and the importance of applying research ethics in an educational context. This analysis shows that educational research requires many different methodological approaches and designs to suit the objectives, type of problem, and research context. Apart from that, research ethics is also very important in every phase of educational research, from planning, data collection, to reporting results. To maintain the credibility and credibility of research, ethics such as scientific honesty, respect for research subjects, and data protection are essential. Therefore, having a balanced understanding of the methodological and ethical elements of research will help produce educational research that is quality, honest, and contributes positively to educational development.